2008
DOI: 10.1523/jneurosci.2882-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for Onset and Sustained Activity in the Neuronal Code for Temporal Periodicity and Acoustic Envelope Shape

Abstract: Auditory neurons are selective for temporal sound information that is important for rhythm, pitch, and timbre perception. Traditional models assume that periodicity information is represented either by the discharge rate of tuned modulation filters or synchrony in the discharge pattern. Compelling evidence for an invariant rate or synchrony code, however, is lacking and neither of these models account for how the sound envelope shape is encoded. We examined the neuronal representation for envelope shape and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 67 publications
(82 reference statements)
7
58
0
Order By: Relevance
“…In contrast, previous studies that have looked for an organization for amplitude modulations have focused primarily on rate MTF measurements (Langner et al 2002;Schreiner and Langner 1988). Recently we have demonstrated that synchrony-and rate-tuning patterns are not complementary and can lead to distinctly different neural selectivity (Zheng and Escabi 2008). Thus it is likely that our findings would not be reproducible with rate based MTF approaches.…”
Section: Functional Implicationsmentioning
confidence: 59%
“…In contrast, previous studies that have looked for an organization for amplitude modulations have focused primarily on rate MTF measurements (Langner et al 2002;Schreiner and Langner 1988). Recently we have demonstrated that synchrony-and rate-tuning patterns are not complementary and can lead to distinctly different neural selectivity (Zheng and Escabi 2008). Thus it is likely that our findings would not be reproducible with rate based MTF approaches.…”
Section: Functional Implicationsmentioning
confidence: 59%
“…Nonsynchronized metrics of temporal tuning (mean activity as a function of temporal modulation) and synchronized metrics of temporal tuning (vector strength and STRF-based MTFs) are in prevalent use within the literature, but can show different tuning properties (Eggermont, 2002;Zheng and Escabí, 2008). Consistent with this, recent work in the STG has shown that a nonsynchronized metric and a synchronized metric show lowpass and bandpass tuning, respectively (Pasley et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Within these studies, a wide range of stimuli have been used to characterize temporal tuning, including sinusoidally amplitude-modulated (SAM) tones, SAM noise, moving spectrotemporal ripples, tone pips, harmonic complexes, noise bursts, consonant-vowel pairs, and continuous speech. This variation is relevant because temporal tuning is not invariant to stimulus type (Eggermont, 2002;Malone et al, 2007Malone et al, , 2013Zheng and Escabí, 2008) and differences in temporal tuning in the various studies may be partially attributable to the vast array of stimulus types used to characterize the system. In this study, we use speech stimuli to determine temporal tuning in the STG and thus characterize temporal processing relevant for speech processing in the STG.…”
Section: Discussionmentioning
confidence: 99%
“…As with any sinusoidal modulation, the envelope shape of a single cycle including its slope (rising and falling) and its duration vary when the modulation frequency is varied. Therefore, one cannot examine how neurons respond to independent variation in shape and modulation frequency by utilizing SAM sounds, as we previously explained (Zheng and Escabí 2008). To overcome this limitation, in this study we created a set of periodic basis spline (B-spline) sequences allowing independent control of the sound envelope shape and modulation frequency (see Fig.…”
Section: Periodic B-spline Shaped Noise Sequencementioning
confidence: 99%